2018
DOI: 10.1055/s-0038-1668577
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Ripening Using Foley Balloon with or without Oxytocin: A Systematic Review and Meta-Analysis

Abstract: Adding oxytocin to FB at the time of preinduction cervical ripening does not reduce cesarean rates nor improve maternal or neonatal outcomes. Multiparous women who received FB alone seem to have lower rates of vaginal deliveries within 24 hours, but these results should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
(72 reference statements)
0
16
0
1
Order By: Relevance
“…They observed lower TID, and a higher rate of delivery <24 h in the group with combined catheter and oxytocin. A recent meta-analysis has also demonstrated that simultaneous use of oxytocin with a Foley catheter could shorten induction to delivery time and increase deliveries within 12 to 24 h [ 20 ]. The adjunction of oxytocin is likely to favor a synergistic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed lower TID, and a higher rate of delivery <24 h in the group with combined catheter and oxytocin. A recent meta-analysis has also demonstrated that simultaneous use of oxytocin with a Foley catheter could shorten induction to delivery time and increase deliveries within 12 to 24 h [ 20 ]. The adjunction of oxytocin is likely to favor a synergistic action.…”
Section: Discussionmentioning
confidence: 99%
“…As concomitant administration of prostaglandin and oxytocin is strictly forbidden to prevent the risk of tachysystolia or uterine hyperstimulation [ 21 ], oxytocin may be administrated earlier when used in combination with mechanical devices, positively impacting the period of time before birth. Finally, the combination of catheter plus oxytocin has not been shown to impact rates of caesarean section, postpartum hemorrhage, or neonatal complications [ 19 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the mechanical methods, the most popular is the Foley catheter 89, 90 , either alone 91 or in association with oxytocin 9296 , or misoprostol 97, 98 , and with different balloon volumes 99, 100 . The combination of mechanical and pharmacological methods used simultaneously does not show clear benefits in terms of mode of delivery: the use of the Foley catheter with oxytocin increases the rate of delivery within 24 hours in nulliparas 95, 96 , while the association of Foley and misoprostol 101 reduces the intervention to delivery time interval and the number of uterine hyperstimulations, in both cases without influencing cesarean delivery rates.…”
Section: Methods Of Inductionmentioning
confidence: 99%
“…9e12 Similarly, a systematic review and meta-analysis found that dual agent ripening with Foley catheter and oxytocin decreased time to delivery without increase in maternal and neonatal adverse outcomes compared with Foley alone. 13 Overall, these studies provided high-quality evidence to support the use of dual agent cervical ripening methods for labor induction.…”
mentioning
confidence: 89%